TGFBI secreted by mesenchymal stromal cells ameliorates osteoarthritis and is detected in extracellular vesicles. (January 2020) - Ruiz, Maxime; Toupet, Karine; Maumus, Marie; Rozier, Pauline; Jorgensen, Christian; Noël, Danièle
Abstract: Mesenchymal stem/stromal cells (MSCs) are of interest in the context of osteoarthritis (OA) therapy. We previously demonstrated that TGFβ-induced gene product-h3 (TGFBI/BIGH3) is downregulated in human MSCs (hMSCs) from patients with OA, suggesting a possible link with their impaired regenerative potential. In this study, we investigated TGFBI contribution to MSC-based therapy in OA models. First, we showed that co-culture with murine MSCs (mMSCs) partly restored the expression of anabolic markers and decreased expression of catabolic markers in OA-like chondrocytes only upon priming by TGFβ3. Moreover, TGFβ3-primed hMSCs not only modulated the expression of anabolic and catabolic markers, but also decreased inflammatory factors. Then, we found that upon TGFBI silencing, mMSCs partly lost their inductive effect on chondrocyte anabolic markers. Injection of hMSCs in which TGFBI was silenced did not protect mice from OA development. Finally, we showed that MSC chondroprotection was attributed to the presence of TGFBI mRNA and protein in extracellular vesicles. Our findings suggest that TGFBI is a chondroprotective factor released by MSCs and an anabolic regulator of cartilage homeostasis.